Pengaruh E-Commerce, Literasi Keuangan Dan Permodalan Terhadap Kinerja Umkm Di Kota Mataram - Raehan Nurbayani; Ni Nyoman Yuliati (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2024)
The use of E-commerce, financial literacy and capital can influence the performance of UMKM. This research aims to determine the influence of E-commerce, financial literacy and capital on the performance of UMKM in Mataram City. This research is associative research with a quantitative approach. This research consists of three independent variables, namely E-Commerce (X1), Financial Literacy (X2) and Capital (X3) as well as one dependent variable MSME Performance (Y). The population in this research is UMKM actors in Mataram City. The sample was determined using a random sampling method where the total population was 22,473 UMKM actors and a sample of 100 samples could be determined. Data were analyzed using Multiple Linear Regression using the SPSS program version 25. The results of this research show that the independent variable E-commerce has a significant effect on the performance of UMKM. Financial literacy has a significant effect on UMKM performance and capital has a significant effect on UMKM performance.